2018
DOI: 10.1080/01605682.2017.1409867
|View full text |Cite
|
Sign up to set email alerts
|

An alternative approach to decompose the potential gains from mergers

Abstract: Bogetoft and Wang (2005) proposed admirable production economic models to estimate and decompose the potential gains from mergers. They provided a good platform to quantify the merger efficiency and related it to relevant organizational changes ex-ante. In this paper, we develop an alternative approach to decompose the potential overall gains from mergers into to technical effect, size effect and harmony effect. The proposed approach uses strongly efficient projections, and consistently calculates radial input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 18 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…Bogetoft and Wang (2005) used the DEA model to examine the gains from a merger and further decomposed the gains into a technical efficiency index, a harmony index and a size index. Based on Bogetoft and Wang's approach, Li et al (2018a) proposed a DEA-based alternative approach to re-decompose the potential overall gains. Johnes and Yu (2008) evaluated the merger efficiency of Chinese higher education by proposing DEA models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bogetoft and Wang (2005) used the DEA model to examine the gains from a merger and further decomposed the gains into a technical efficiency index, a harmony index and a size index. Based on Bogetoft and Wang's approach, Li et al (2018a) proposed a DEA-based alternative approach to re-decompose the potential overall gains. Johnes and Yu (2008) evaluated the merger efficiency of Chinese higher education by proposing DEA models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since its seminal work in Charnes et al (1978) and Banker et al (1984), the DEA methodology has attracted more and more attention from scholars all over the world, and the DEA methodology and its applications have been extensively studied in the literature (Emrouznejad, 2014;Emrouznejad & Yang, 2018). On the application aspect, the literature has witnessed DEA-based approaches in different areas from public sector such as universities, hospitals, sports, and disaster relief operations to private sector such as banks, supply chains, manufacturing industries, and mergers and acquisitions (An, Meng, Ang, & Chen, 2018;Li, Liang, Li, & Emrouznejad, 2018a;Li, Zhu, & Zhuang, 2018e). On the methodology aspect, many innovative concepts and models have been proposed to extend and enrich the DEA theory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A two-phase method suggested to estimate of the potential merger efficiency of a hypothetical unit from the cost viewpoint by Shi et al [43]. Also, a new method is proposed for analyzing the potential overall gains from mergers into technical, size, and harmony effects by Li et al [36]. According to this study, it was concluded that the technical and harmony effects would work favor mergers, while the size effect would work against most mergers.…”
Section: Introductionmentioning
confidence: 99%